2019
DOI: 10.3390/jcm8091284
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Profiles of the Methylome and Transcriptome in Peripheral Blood Mononuclear Cells of Rheumatoid Arthritis

Abstract: Using next-generation sequencing to decipher methylome and transcriptome and underlying molecular mechanisms contributing to rheumatoid arthritis (RA) for improving future therapies, we performed methyl-seq and RNA-seq on peripheral blood mononuclear cells (PBMCs) from RA subjects and normal donors. Principal component analysis and hierarchical clustering revealed distinct methylation signatures in RA with methylation aberrations noted across chromosomes. Methylation alterations varied with CpG features and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…In addition, FOLR3 and IL1B were upregulated in CD14 + Mos of different patients. FOLR3 is involved in rheumatoid arthritis ( Tseng et al., 2019 ) and SARS-CoV-2 ( Sfikakis et al., 2021 ), but its relationship with pSS has not been reported. According to data from this study, it was found that FOLR3 showed the opposite trend of IL1B expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FOLR3 and IL1B were upregulated in CD14 + Mos of different patients. FOLR3 is involved in rheumatoid arthritis ( Tseng et al., 2019 ) and SARS-CoV-2 ( Sfikakis et al., 2021 ), but its relationship with pSS has not been reported. According to data from this study, it was found that FOLR3 showed the opposite trend of IL1B expression.…”
Section: Discussionmentioning
confidence: 99%
“…Huo et al [ 22 ] determined that abnormal methylation of CDC20 and CCNA2 may be effective in predicting the prognosis of RA with microarray combined with bioinformatics analysis. For RA, some studies combing microarray with bioinformatics analysis have revealed differential methylation signals at S100A6 and EFCAB4B promoter regions in the whole blood [ 23 ], CD86, RAB20, XAF1, FOLR3, LTBR, KCNH8, DOK7, PDGFA, PITPNM2, and CELSR1 in B cells [ 24 ], and IFN related genes (IFIT1, IRF7, MX1, OAS1, USP18, RSAD2, IFI44L) in CD4+ T cells [ 25 ]. However, until now, the methylation of RA-related genes are still insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Rab20 up-regulation may contribute to plaque destabilization via increased autophagy and cell death ( Cederstrom et al, 2020 ). High Rab20 levels promote B cell activation and facilitate rheumatoid arthritis development ( Tseng et al, 2019 ). Rab20’s expression was increased during B cell transformation by a polymorphism associated with Crohn’s disease and vaccination ( Mehta et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%